2021
DOI: 10.3389/fphar.2021.625386
|View full text |Cite
|
Sign up to set email alerts
|

Nigella Plants – Traditional Uses, Bioactive Phytoconstituents, Preclinical and Clinical Studies

Abstract: Nigella is a small genus of the family Ranunculaceae, which includes some popular species due to their culinary and medicinal properties, especially in Eastern Europe, Middle East, Western, and Central Asia. Therefore, this review covers the traditional uses and phytochemical composition of Nigella and, in particular, Nigella sativa. The pharmacological studies reported in vitro, in vivo, and in humans have also been reviewed. One of the main strength of the use of Nigella is that the seeds are rich in the ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 222 publications
1
32
2
4
Order By: Relevance
“…For the chemical composition, it was reported that N. sativa contains more bioactive compounds like phenolic acids, flavonoids, and thymoquinone considered responsible for its biological activities. These compounds have not been identified in N. orientalis and might explain the differences in our obtained results (Farag, Gad, Heiss, & Wessjohann, 2014; Salehi et al, 2021).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…For the chemical composition, it was reported that N. sativa contains more bioactive compounds like phenolic acids, flavonoids, and thymoquinone considered responsible for its biological activities. These compounds have not been identified in N. orientalis and might explain the differences in our obtained results (Farag, Gad, Heiss, & Wessjohann, 2014; Salehi et al, 2021).…”
Section: Discussioncontrasting
confidence: 69%
“…These compounds have not been identified in N. orientalis and might explain the differences in our obtained results (Farag, Gad, Heiss, & Wessjohann, 2014;Salehi et al, 2021).…”
Section: Effect Of Noo On the Viability Of Raw 2647 Murine Macrophagescontrasting
confidence: 69%
“…Decreased viral load and improved liver function were similarly reported in another study by Barakat et al (2013) where HCV patients received capsules of Nigella sativa oil (450 mg) three times a day over 3 months. Furthermore, Thymoquinone has been studied for benefits other than anti-inflammatory effects which are beyond the scope of this review ( Mostofa et al, 2017 ; Mohammed and Islam, 2018 ; Shanmugam et al, 2018 ; Jehan et al, 2020 ; Leong et al, 2021 ; Salehi et al, 2021 ).…”
Section: Scientific Reportmentioning
confidence: 99%
“…A metabolite library of 54 structurally diverse phytomolecules was constructed through a literature survey to identify potential CHIKV treatments [17,18] (Supplementary Table 1). The chemical and structural properties such as molecular weight, chemical formula, and canonical smiles of these metabolites were retrieved from the PubChem Database [19].…”
Section: Metabolite Librarymentioning
confidence: 99%